The Conciliation in the State Demands as an Alternative for the Economy in the Process in New Civil Procedure Code - Camb, Eduardo Augusto Salomão (2016)
The present study deals with the possibility of conciliation in the demands that involve the Public Power, having as main objective the procedural economy, both as regards the faster process, as to reduction of expenses with the structure of the Judiciary. Despite of the unavailability of the public interest, seeks out the adequacy of this principle with the principles in the New Civil Procedure Code, which encourages conciliation as a means of settling disputes.